2014
DOI: 10.1007/s12078-014-9170-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Self-Reported Olfactory Function in a Home-Based Study of Independent-Living, Healthy Older Women

Abstract: Introduction The 2011–14 US National Health and Nutrition Examination Survey chemosensory protocol asks adults to self-rate their orthonasal (via nostrils) and retronasal (via mouth) smell abilities for subsequent odor identification testing. From data collected with a similar protocol, we aimed to identify a self-reported olfactory index that showed the best sensitivity (correctly identifying dysfunction) and specificity (correctly indentifying normosmia) with measured olfaction. Methods In home-based testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 45 publications
6
47
3
3
Order By: Relevance
“…The questionnaire was adapted from previous research, including a community-based study of self-rated olfaction in older adults [10], the olfaction and taste questionnaire used in the Beaver Dam Studies [11, 12], and the self-reported chemosensory questionnaire used in the Disability Supplement to the 1994 National Health Interview Survey [13]. The CSQ was content-validated by a nationwide team of chemosensory experts and cognitively tested for response problems and cultural appropriateness to ensure that respondents could understand, process, and interpret the questions in a consistent manner as intended.…”
Section: The Chemosensory Questionnaire (Csq) For Nhanes 2011–2014mentioning
confidence: 99%
See 4 more Smart Citations
“…The questionnaire was adapted from previous research, including a community-based study of self-rated olfaction in older adults [10], the olfaction and taste questionnaire used in the Beaver Dam Studies [11, 12], and the self-reported chemosensory questionnaire used in the Disability Supplement to the 1994 National Health Interview Survey [13]. The CSQ was content-validated by a nationwide team of chemosensory experts and cognitively tested for response problems and cultural appropriateness to ensure that respondents could understand, process, and interpret the questions in a consistent manner as intended.…”
Section: The Chemosensory Questionnaire (Csq) For Nhanes 2011–2014mentioning
confidence: 99%
“…Self-reported smell function typically has not been considered to be a sensitive indicator of measured impairment [10]. However, previously reported low sensitivities of self-reported smell function may have resulted from the use of a single question, which simply asked participants to rate their current smell ability [11, 15].…”
Section: The Chemosensory Questionnaire (Csq) For Nhanes 2011–2014mentioning
confidence: 99%
See 3 more Smart Citations